Ionotropic and metabotropic glutamate receptor mediation of glucocorticoid-induced apoptosis in hippocampal cells and the neuroprotective role of synaptic N-methyl-D-aspartate receptors - Lu, J. (2003)
Glutamate receptors have been proposed to mediate the apoptotic actions of glucocorticoids in hippocampal cells. To further analyze the role of glutamate receptors in this process, we pretreated primary hippocampal cells from neonatal (postnatal day 4) rats with antagonists of ionotropic glutamate receptor (iGluR) and metabotropic glutamate receptor (mGluR) antagonists before exposure to the specific glucocorticoid receptor agonist dexamethasone (DEX) at a dose of 1 μM. Dizocilpine (MK801; a general N-methyl-Daspartic acid [NMDA] receptor antagonist, NMDAR antagonist) and ifenprodil (a specific ligand of the NMDAR 2B subunit, NR2B), were used to block iGluR; (RS)-α-ethyl-4-carboxyphenylglycine (E4CPG) and (RS)-α-cyclopropyl-4- phosphonophenyl-glycine (CPPG) were employed as I/II (E4CPG) and II/III (CPPG) mGluR antagonists. Blockade of iGluR resulted in a significant attenuation of DEX-induced cell death; the finding that ifenprodil exerted a similar potency to MK801 demonstrates the involvement of NR2B receptors in glucocorticoid-induced cell death. Apoptosis accounted for a significant amount of the cell loss observed, as detected by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling histochemistry for the in situ labeling of DNA breaks; apoptotic cells were distinguished from necrosis on the basis of morphological criteria, including chromatin condensation, membrane blebbing and presence of apoptotic bodies. Treatment with E4CPG and CPPG completely abolished the apoptotic response to DEX, thus showing the additional contribution of mGluR to the phenomenon. Further, dose-response studies with NMDA revealed that whereas high (10 μM) doses of NMDA themselves elicit cytotoxic responses, low (1–5 μM) concentrations of NMDA can effectively oppose DEX-induced cell death. Interestingly, the neuroprotective actions of low dose NMDA stimulation were abolished when either synaptic or extrasynaptic NMDA receptors were blocked with MK801 in combination with the GABA receptor antagonist bicuculline (synaptic) or ifenprodil (extrasynaptic). In summary, the present data show that both iGluR and mGluR mediate the neurotoxic effects of glucocorticoids on hippocampal cells and that pre-treatment with low doses of NMDA, by acting on synaptic and extrasynaptic receptors, render hippocampal cells less vulnerable to glucocorticoid insults.